GABAergic neurons of the medial septum play a nodal role in facilitation of nociception-induced affect - Ang, Seok Ting (Sci Rep, 2015)
The present study explored the functional details of the influence of medial septal region (MSDB) on spectrum of nociceptive behaviours by manipulating intraseptal GABAergic mechanisms. Results showed that formalin-induced acute nociception was not affected by intraseptal microinjection of bicuculline, a GABA(A) receptor antagonist, or on selective lesion of septal GABAergic neurons. Indeed, the acute nociceptive responses were dissociated from the regulation of sensorimotor behaviour and generation of theta-rhythm by the GABAergic mechanisms in MSDB. The GABAergic lesion attenuated formalin-induced unconditioned cellular response in the anterior cingulate cortex (ACC) and blocked formalin-induced conditioned place avoidance (F-CPA), and as well as the contextual fear induced on conditioning with brief footshock. The effects of lesion on nociceptive-conditioned cellular responses were, however, variable. Interestingly, the lesion attenuated the conditioned representation of experimental context in dorsal hippocampus field CA1 in the F-CPA task. Collectively, the preceding suggests that the MSDB is a nodal centre wherein the GABAergic neurons mediate nociceptive affect-motivation by regulating cellular mechanisms in ACC that confer an aversive value to the noxious stimulus. Further, in conjunction with a modulatory influence on hippocampal contextual processing, MSDB may integrate affect with context as part of associative learning in the F-CPA task.